Simulation model of unity power factor uninterruptible power supply topology using single-phase matrix converter - Muhammad Shawwal Mohamad Rawi; Rahimi Baharom; Nur Hidayah Abdullah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper presents a computer simulation model of the unity power factor uninterruptible power supply (UPS) topology using single-phase matrix converter (SPMC) that focuses on the switching integration for both rectifier and inverter operations. The proposed integrated switches capable of controlling the SPMC to operate as a rectifier operation to charge the DC battery during the normal operation and to switch the SPMC to operate as an inverter during power outage conditions continuously and instantaneously using a single power converter circuit. The use of a single power converter circuit can solve the typical UPS system that requires at least two separate power converter circuits, thus contributing to the higher power semiconductor losses and complicated control circuits. With the proposed circuit topology, it can improve the power density of the power electronics converter system resulting in low power losses. The active power filter (APF) function has been used to improve the supply current waveform to follow the shape of the sinusoidal reference current to be in phase with the supply voltage waveform, thus reduce the total harmonic distortion (THD) level and improve the power factor. To verify the proposed operation, the selected simulation results are presented, and the proposed work has been done through the MATLAB/Simulink.